Hotelaria de Charme e os Desafios da Agenda para o Desenvolvimento Sustentável no Turismo / Charm Hotels and the Challenges of Sustainable Development Agenda in Tourism - Urt, Maria Caroline Moron (2017)
RESUMOA hotelaria de charme representa um segmento do trade turístico que tem como propósito conciliar qualidade nos serviços oferecidos, o charme inerente ao hotel e ao seu entorno, além da preocupação com o desenvolvimento sustentável. No Brasil, a hotelaria de charme é capitaneada pela Associação de Hotéis Roteiros de Charme, que tem no seu Código de Ética e Conduta Ambiental [CECA] o principal instrumento para estimular os meios de hospedagem à empreenderem ações voltadas ao desenvolvimento sustentável. Assim, o presente artigo teve como objetivo analisar o modo como os estímulos provenientes da Associação de Hotéis Roteiros de Charme alinham-se com a agenda para o desenvolvimento sustentável no turismo. Além de consulta a documentos, relatórios e ao CECA, foram realizadas duas entrevistas em profundidade, com o presidente e o diretor de Sustentabilidade da Associação. De um modo geral, detectou-se a necessidade de ações voltadas ao desenvolvimento local e ao empoderamento de grupos em situação de vulnerabilidade social para que a hotelaria de charme seja, de fato, mais alinhada à agenda para o desenvolvimento sustentável no turismo. PALAVRAS-CHAVETurismo. Hotelaria de Charme. Desenvolvimento Sustentável. Código de Ética e Conduta Ambiental [CECA] Charm Hotels. ABSTRACTCharm hotels represent a tourism segment that aims to harmonize quality in the services offered to tourists, the charm inherent to the hotel and its surroundings, as well as the concern with sustainable development. In Brazil, the segment of charm hotels is captained by the Association of Hotels Roteiros de Charme, which has in its Code of Ethics and Environmental Conduct (CEEC, in English) the main instrument to stimulate the associated lodging facilities to undertake actions to promote sustainable development. In this sense, the present article aimed to analyze how the stimuli coming from the Association of Hotels Roteiros de Charme are aligned with the agenda for sustainable development in tourism. To this end, in addition to consulting documents, reports and the CEEC, two in-depth interviews were conducted with the president and the sustainability director of the Association of Hotels Roteiros de Charme. In general, we verified the need for actions to promote the local development and the empowerment of groups in a situation of social vulnerability, with the aimed that charm hotels will be aligned with the contemporary agenda for sustainable development in tourism. KEYWORDSTourism. Charm Hotels. Sustainable Development. Code of Ethics and Environmental Conduct [CEEC]. AUTORESMaria Caroline Moron Urt – Mestra em Administração pela Universidade Federal de Mato Grosso do Sul, Campo Grande-MS, Brasil. Currículo:  http://lattes.cnpq.br/2972819931927667. E-mail: m.carol.urt@gmail.com Dyego de Oliveira Arruda – Doutor. Professor no Centro Federal de Educação Tecnológica Celso Suckow da Fonseca (CEFET-RJ), Valença-RJ, Brasil. Currículo: http://lattes.cnpq.br/5222976964204691. E-mail: dyego.arruda@gmail.com Milton Augusto Pasquotto Mariani – Doutor. Professor e pesquisador na Escola de Administração e Negócios, no Programa de Pós-Graduação em Administração e no Mestrado Profissional em Estudos Fronteiriços, todos na Universidade Federal de Mato Grosso do Sul, Campo Grande-MS, Brasil. Currículo: http://lattes.cnpq.br/0935409945176042. E-mail: miltmari@terra.com.br REFERÊNCIASAggett, M. (2007). What has influenced growth in the UK’s boutique hotel sector? International Journal of Contemporary Hospitality Management, 19(2): 169-177.Borges, C. H. L.; Ferraz, M. I. F. & Borges, A. V. B. (2015). Turismo sustentável e meios de hospedagem: uma avaliação da sustentabilidade hoteleira em Barra Grande, Maraú (BA). Revista Turismo - Visão e Ação, 17(3), 601-629.Brandi, C. A. (2017). Sustainability standards and sustainable development: synergies and trade-offs of transnational governance. Sustainable Development, 25(1), 25-34.Buckley, R. (2012). Sustainable tourism: research and reality. Annals of Tourism Research, 39(2), 528-546.Cardoso, L. C.; Alperstedt, G. D.; Costa, J. I. P. & Mondo, T. S. (2011). Internacionalização e gestão ambiental: um estudo nos meios de hospedagem vinculados à Associação Roteiros de Charme em Santa Catarina, Brasil. Revista de Investigación en Turismo y Desarollo Local, 4(10), 1-26.CNUMAD - Conferência das Nações Unidas para o Meio Ambiente e Desenvolvimento (1995). Agenda 21. Câmara dos Deputados.  Brasília: Coordenação de Publicações.Deacon, B. (2016). SDGs, Agenda 2030 and the prospects for transformative social policy and social development. Journal of International and Comparative Social Policy, 32(2), 79-82.Elkington, J. (1997). Cannibals with forks: The triple bottom line of 21st century business. Oxford: Capstone Publishing.Flick, U. (2009). An introduction to qualitative research. London: Sage Publications.Georgea, C. (1999). Testing for sustainable development through environmental assessment. Environmental Impact Assessment Review, 19(2), 175-200.Holden, E.; Linnerud, K. & Banister, D. (2017). The imperatives of sustainable development. Sustainable Development, 25(3), 213-226.Hopwood, B.; Mellor, M. & O’Brien, G. (2005). Sustainable development: mapping different approaches. Sustainable Development, 13(1), 38-52.Hugues, E. & Scheyvens, R. (2016). Corporate social responsibility in tourism post-2015: A development first approach. Tourism Geographies, 18(5), 469-482.Jones, D. L.; Day, J. & Quadri-Felitti, D. (2013). Emerging definitions of boutique and lifestyle hotels: a delphi study. Journal of Travel & Tourism Marketing, 30(7), 715–731.Kemp, R. & Martens, P. (2007). Sustainable development: how to manage something that is subjective and never can be achieved? Sustainability: Science, Practice, & Policy, 3(2), 5-14.Kleinrichert, D.; Ergul, M.; Johson, C. & Uydaci, M. (2012). Boutique hotels: technology, social media and green practices. Journal of Hospitality and Tourism Technology, 3(3), 211-225.Lara, S. B. (2001). Marketing & vendas na hotelaria. São Paulo: Futura.Lélé, S. M. (1991). Sustainable development: A critical review. World Development, 19(6), 607-621.Lim, W. M. & Endean, M. (2009). Elucidating the aesthetic and operational characteristics of UK boutique hotels. International Journal of Contemporary Hospitality Management, 21(1), 38-51.Malta, M. C. M.; Mariani, M. A. P. & Arruda, D. O. (2013). Reflexões acerca da sustentabilidade no âmbito da gestão de empreendimentos hoteleiros. Revista Brasileira de Ecoturismo, 6(2), 534-553.McIntosh, A. J. & Siggs, A. (2005). An exploration of the experiential nature of boutique accommodation. Journal of Travel Research, 44(1): 74-81.Molina-Aorín, J. F.; Claver-Cortés, E.; Pereira-Moliner, J. & Tari, J. J. (2009). Environmental practices and firm performance: an empirical analysis in the Spanish hotel industry. Journal of Cleaner Production, 17(5), 516-524.Neto, F. (2003). A new approach to sustainable tourism development: moving beyond environmental protection. A United Nations Sustainable Development Journal, 27(3), 212-222.Prudhomme, B. & Raymond, L. (2016). Implementation of sustainable development practices in the hospitality industry: a case study of five Canadian hotels. International Journal of Contemporary Hospitality Management, 28(3), 609-639.Roteiros de Charme (2017a). Quem somos - roteiros de charme.Roteiros de Charme (2017b). Código de Ética e Conduta Ambiental.Saarinen, J. (2006). Traditions of sustainability in tourism studies. Annals of Tourism Research, 33(4), 1121-1140.Sampaio, C. A. C. (2001). Turismo: sob uma análise do desenvolvimento sustentável. Turismo: Visão e Ação, 4(8), 29-44.Silva, D. R. F. & Mota, K. C. N. (2010). O segmento da hotelaria de charme como estratégia mercadológica no Ceará. Anais… 6º Seminário de Pesquisa em Turismo do Mercosul, UCS, Caxias do Sul, p. 1-14.Silveira, M. A. T. (2005). Turismo y sustentabilidad: entre el discurso y la acción. Estudios y Perspectivas en Turismo, 14(3), 222-242.Sims, R. (2009). Food, place and authenticity: local food and the sustainable tourism experience. Journal of Sustainable Tourism, 17(3), 321-336.Stake, R. E. (2000). Case Studies. In: Denzin, N. K. & Lincoln, Y. S. (orgs) Handbook of qualitative research, p. 435-454. London: Sage Publications.Stebbins, R. A. (2001). Exploratory research in the social sciences. London: Sage Publications.Tao, T. C. H. & Wall, G. (2009). Tourism as a sustainable livelihood strategy. Tourism Management, 30(1), 90-98.UNCSD - United Nations Conference on Sustainable Development (2012). The Future We Want. United Nations, New York.UNDP - United Nation Development Programme (2015). The Millennium Development Goals Report – 2015. New York: UNDP.UNEP/WTO - United Nations Environment Programme and World Tourism Organization (2005). Making Tourism More Sustainable: A Guide for Policy Makers. Madrid: UNEP/WTOUNFCCC - United Nations Framework Convention on Climate Change (1998). Kyoto Protocol. New York: UNFCCC.United Nations (2017). Sustainable Development Goals - 17 Goals to Transform our World.UNWTO – World Tourism Organization (2016). The tourism sector and the Sustainable Development Goals: responsible tourism, a global commitment. Madrid: UNWTO.WCED – World Commission on Environment and Development (1987). Report of the World Commission on Environment and Development: Our Common Future. London: Oxford University Press.WTTC - World Travel & Tourism Council (2016a). Economic Impact 2016: Annual Update Summary. London: WTTC.WTTC - World Travel & Tourism Council (2016b). Economic Impact 2016: Brazil. London: WTTC.Zambon, M. C. F. A. (2009). Diretrizes para a criação de marcas emocionais em empreendimentos da hotelaria de charme: um estudo multicaso dos filiados da Associação de Hotéis Roteiros de Charme em Santa Catarina. Tese. Doutorado em Engenharia de Produção, Universidade Federal de Santa Catarina, Florianópolis. RECEBIDO em: 17 JUL 2017. ACEITO em 16 NOV 2017